Influence of genomic structural variations and nutritional conditions on the emergence of quorum sensing-dependent gene regulation defects in Burkholderia glumae - Kang, Minhee; Lim, Jae Yun; Kim, Jinwoo; Hwang, Ingyu; Goo, Eunhye (Frontiers in Microbiology, 2022)
Bacteria often change their genetic and physiological traits to survive in harsh environments. To determine whether, in various strains of Burkholderia glumae, genomic diversity is associated with the ability to adapt to ever-changing environments, whole genomes of 44 isolates from different hosts and regions were analyzed. Whole-genome phylogenetic analysis of the 44 isolates revealed six clusters and two divisions. While all isolates possessed chromosomes 1 and 2, strains BGR80S and BGR81S had one chromosome resulting from the merging of the two chromosomes. Upon comparison of genomic structures to the prototype BGR1, inversions, deletions, and rearrangements were found within or between chromosomes 1 and/or 2 in the other isolates. When three isolates—BGR80S, BGR15S, and BGR21S, representing clusters III, IV, and VI, respectively—were grown in Luria-Bertani medium, spontaneous null mutations were identified in qsmR encoding a quorum-sensing master regulator. Six days after subculture, qsmR mutants were found at detectable frequencies in BGR15S and BGR21S, and reached approximately 40% at 8 days after subculture. However, the qsmR mutants appeared 2 days after subculture in BGR80S and dominated the population, reaching almost 80%. No qsmR mutant was detected at detectable frequency in BGR1 or BGR13S. The spontaneous qsmR mutants outcompeted their parental strains in the co-culture. Daily addition of glucose or casamino acids to the batch cultures of BGR80S delayed emergence of qsmR mutants and significantly reduced their incidence. These results indicate that spontaneous qsmR mutations are correlated with genomic structures and nutritional conditions.